The Right To Life Or The Right To Compensation Upon Death: Perspectives On An Inclusive Understanding Of The Constitutional Right To Life In Nigeria - Enabulele, Amos O. (Journal of Sustainable Development Law and Policy, 2025)
This paper discusses the right to life in its most inclusive sense. It argues that the right to life cannot be seen only in the light of the deprivation of life, but more importantly, in the light of the sustenance of life. Accordingly, that the right to life should be broadly interpreted to encompass all its components and that some of its important components are contained in the non-justiciable provisions of our Constitution. The paper further argues that by assimilating the provisions which the Constitution declares non-justiciable with the right to life, such provisions become justiciable without disturbing the their otherwise non-justiciable character since they are not enforced on their own force but on the force of the justiciable right to life provisions of the Constitution.